Effectiveness of Tepid Sponging with Antipyretic Drugs Versus Antipyretic Drugs Alone in Managing Fever in Children - Alex, Ashna Mary; Naregal, Prakash; Mohite, Vaishali Rajsinh; Pawar, Shivaji; Pawar, Sunita (Journal of Neonatal Surgery, 2025)
Introduction: Increased body temperature is a common symptom in children, often requiring medical intervention to alleviate discomfort and prevent complications. Tepid sponging and antipyretic drugs are commonly used to manage fever. This study aimed to compare the effectiveness of using both tepid sponging and antipyretic drugs versus antipyretic drugs alone in reducing fever among children at Krishna Hospital, Karad. Methods: True experimental research was undertaken at Krishna Hospital, Karad. Children aged 6 months-12 years presenting with fever were included. 60 children were randomly assigned to either the intervention group (tepid sponging along with antipyretic drugs) 30 Children or the control group (antipyretic drugs alone) 30 children. The intervention group received tepid sponging using lukewarm water in addition to the prescribed antipyretic drug. The control group was provided with only the prescribed antipyretic drug. The initial temperature measurement was taken at 0 minutes. If the child was in the group receiving both tepid sponging and an antipyretic drug, paracetamol was administered, and tepid sponging was performed for 15 minutes. The temperature was then rechecked at the 15-minute mark. Children from the antipyretic drug-only group will receive paracetamol and subsequently, the temperature was monitored. Fever resolution time, reduction in temperature, and improvement in subjective symptoms were evaluated as primary outcome measures. Results: The outcome of the study shows that there was no significant difference in the reduction of body temperature between the combined group (tepid sponging and antipyretic drug) and the control group (antipyretic drug alone) 15 minutes after the intervention. However, starting from 30 minutes and continuing at 45, 60, 90, and 120 minutes, the study group showed a greater reduction in temperature compared to the control group. This difference in temperature reduction was found to be statistically significant (p<0.0001), indicating that the use of tepid sponging with antipyretic drug was more effective in decreasing fever in children compared to antipyretic drug alone. These findings suggest that tepid sponging can be a beneficial adjunctive intervention for fever management in pediatric patients. Conclusion: The study supports the notion that combining tepid sponging with antipyretic drugs can be a beneficial treatment for managing fever in children. These results can guide healthcare professionals in making evidence-based decisions and recommendations for fever management in pediatric patients